Contribution of Porto Alegre's fairs in the formation of the Licensing in Rural Education - Tatiana Vieira Rodriguês; Marilisa Bialvo Hoffmann; Saul Benhur Schirmer (Universidade Federal do Norte do Tocantins, 2020)
This article intends to understand how the understanding of the processes inherent to the institutionalization and functioning of organic fairs can contribute to the training of the licencing in Rural Education - Science of Nature. In the same way, it is sought to analyze, from the dialogue with different subjects representatives of the organic fairs of Porto Alegre-RS, what aspects the licencing in Rural Education would need to develop to contribute in the management of community processes of organic fairs communities in which they operate. The analysis of the interviews was carried out with methodological aid of the Discursive Textual Analysis (ATD). The results point to the Organic Fairs as an important study space, presenting several formative possibilities. It is important to highlight the need for the fairs to be more approached in the formation of the educator of the field, as a research instrument, as well as teaching and extension, thus contributing to a better understanding of the work universe of the rural people, among them the subjects of agriculture family.